Advanced separations by specialized sorbents - Dragan, Ecaterina Stela (Taylor & Francis, 2014)
Advanced Separations by Specialized Sorbents opens a new window into sorbent materials, presenting fundamental principles for their syntheses and adsorption properties. The book presents advanced techniques used to create specialized sorbents with a wide range of functions that can be used to enhance the separation and/or purification of useful bioactive compounds, heavy metals, dyes, and other substances. It discusses the most recent developments in the field of separation processes, covering specialized sorbents such as monolith cryogels, composite hydrogels, metal-impregnated ion exchangers.
"A CRC title."
Keywords: Separation (Technology); Sorbents.; elektronické knihy; electronic books